Гегемонная маскулинность как фактор мужского (не)здоровья - Кон, И. (Социология: теория, методы, маркетинг, 2008)
Men’s health as a global social problem (in difference from men’s diseases) has emerged in the world science in the 1970s as an aspect of feminist gender studies. After that, a lot of biomedical and social studies of the male psychology, including men’s attitudes to their bodies, health, illnesses and safety, were done. According to the theories of hegemonic masculinity (Reiwyn Connell) and masculine ideology (Donald Levant), one of the most detrimental socio-psychological factors of men’s (un)health are traditional stereotypes of masculinity. The empirical bases and some andrological and sexual medicine connotations of this research are discussed.